Maternal glycemic parameters and adverse pregnancy outcomes among high-risk pregnant women. Issue 1 (13th November 2019) - Zheng, Yanwei; Shen, Yun; Jiang, Susu; Ma, Xiaojing; Hu, Jiangshan; Li, Changbin; Huang, Yajuan; Teng, Yincheng; Bao, Yuqian; Zhou, Jian; Hu, Gang; Tao, Minfang
Abstract : Objective: We aimed to investigate the association between maternal glycemic parameters and adverse pregnancy outcomes among high-risk pregnant women. Research design and methods: A total of 1976 high-risk pregnant women were enrolled between 2015 and 2017. All participants received a 75 g oral glucose tolerance test during the 24–30 gestational weeks and complete birth and delivery information was collected. Adverse pregnancy outcomes were defined as premature birth, birth weight >90th percentile, primary cesarean section, and pre-eclampsia. Logistic regression models were used to assess the association between five maternal glycemic parameters during pregnancy (fasting glucose, 1-hour glucose, 2-hour glucose, HbA1c, and serum 1, 5-anhydroglucitol (1, 5-AG)) and adverse pregnancy outcomes. Results: Of 1976 participants, 498 were diagnosed with gestational diabetes. The multivariable-adjusted ORs of adverse pregnancy outcomes for each one unit increase (1 mmol/L, 1%, or 1 µg/mL) were 2.32 (95% CI 1.85 to 2.92) for fasting glucose, 1.07 (95% CI 1.01 to 1.15) for 1-hour glucose, 1.03 (95% CI 0.96 to 1.10) for 2-hour glucose, 1.77 (95% CI 1.34 to 2.33) for HbA1c, and 0.96 (95% CI 0.94 to 0.98) for 1, 5-AG, respectively. When all five glycemic parameters were simultaneously entered into the multivariable-adjusted model, only fasting glucose was significantly associated with total and individual adverse pregnancy outcomes. Receiver operating characteristic curve showed that fasting glucose plus any one of other four glycemic parameters had significantly enhanced the sensitivity of detecting adverse pregnancy outcomes. Conclusions: Fasting glucose at 24–30 gestational weeks was strongly associated with adverse pregnancy outcomes. Fasting glucose combined with one additional glycemic measurement showed non-inferiority indicating that post-load glycemic measurement was not necessary in detecting adverse pregnancy outcomes among high-risk pregnant women.